PROFIL MUTU KOMODITI UNGGULAN PERKEBUNAN KABUPATEN ENDE (KOMODITI KELAPA) - Emilia S.A. Wangge (Agriculture Faculty of Flores University, 2013)
This research aims at investigating the composition of water and fat contents in coconut commodity in Ende Regency. Coconut commodity profile is useful as the information on business opportunities and investment of coconut commodity cultivation to both foreign and domestic investors as well as the business community so as to spur the growth of investment in Ende. This research was conducted at the Laboratory of Agricultural Technology at Udayana University, Denpasar. From the aspect of quality content on coconut commodity profile in Ende Regency, East Nusa Tenggara Province, it is clear that this area has great potential to be developed.